DINAMIKA POLITIK LOKAL PROVINSI RIAU DALAM SUKSESI KEMENANGAN ANNAS MAAMUN DAN ARSYADJULIANDI RACHMAN TAHUN 2013 - Ahmad Saudi (T JDP (JURNAL DINAMIKA PEMERINTAHAN), 2020)
Abstract This study aims to find out how the dynamics of local politics in the succession of regional leadership in Riau Province by taking a case study of the victory of Annas Maamun and Arsyajuliandi Rahman in the 2013 Riau Regional Head Election. This study uses qualitative research methods and descriptive types. Data collection in this study uses literature study techniques in which the authors take data from books, journals, documents, government sites that are relevant to this research. The results of this study indicate that there is a political dilemma that is found that many people do not exercise their voting rights so that the couple Annas Maamun and Arsyadjuliandi Rachman were elected as Governor of Riau Province. Keywords: Political Dynamics, Riau Province, Regional Head Election, Abstentions